ANALYSIS OF KKNI-OBE CURRICULUM IMPLEMENTATION TO IMPROVE THE QUALITY OF GRADUATES OF MADRASAH IBTIDAIYAH PROSPECTIVE TEACHERS - Misrina, Misrina; Fazilla, Sarah; Fauziana (Program Studi PGMI, 2025)
University management must be carried out effectively so that graduates can have high quality, playing a role as a driver of improving the quality of human resources. One of them can be done by implementing and evaluating the implementation of OBE-based curriculum. This study aims to analyze the implementation of the OBE curriculum at PGMI IAIN Lhokseumawe as an effort to improve the quality of prospective teacher graduates. This study used a qualitative descriptive method with 90 research subjects of PGMI IAIN Lhoksemawe students, data collection was carried out using questionnaires, observation and documentation. Data were analyzed qualitatively by data collection, data condensation, data presentation, and conclusion. The results of the analysis of the OBE curriculum in the IAIN Lhokseumawe PGMI Study Program found that 95% of the curriculum has been prepared according to the OBE principles, for the RPS is still at 40% suitability and needs improvement in Graduate Learning Outcomes (CPL), Course Learning Outcomes (CPMK), and syllabus preparation. For the implementation of Outcome-Based Education (OBE) Curriculum in PGMI Study Program IAIN Lhokseumawe shows that the majority of students assess the implementation of this curriculum is good, it can be concluded that the Curriculum document has been in accordance with the principles of OBE but needs improvement in the preparation of RPS, for the implementation of the OBE curriculum as a whole received a positive response from students.